An exploration of Illinois students' attitudes toward science using multivariate multilevel modeling with a cross‐sectional sample of responses from grades 5 through 10. Issue 8 (2nd April 2019) - Summers, Ryan; Abd‐El‐Khalick, Fouad
Abstract: The present study examined students' attitudes toward science and associated constructs, based on the theories of reasoned action and planned behavior, and explored relationships between individual and school‐related variables common to the research literature. Responses from 1, 291 students in Grades 5 through 10 were collected using the 30‐item Behaviors, Related Attitudes, and Intentions toward Science (BRAINS) Survey along with background information questions. Additional self‐report data were collected from teachers ( n = 56; 82.4%) in participating schools ( n = 68) to obtain information about their education and experience, characteristics and practices, as well as other classroom variables, which could influence students' outlook. Student information, teacher data collected, and other data compiled about participating schools, were used to explore patterns in students' attitudes, beliefs, and intentions. These variables were used to generate multivariate multilevel models through a forward construction process. The final model presented favors individual variables to explain differences in students' responses on all five of the BRAINS subscales, more than group‐level variables captured. Of the predictor variables explored, students' perceived science ability and frequency of talk with family were influential on all subscales, and increasing these variables had a positive effect on the estimated mean scores according to the final model presented. Findings from this study also include commonly observed relationships, such as the decline in attitudes over time, but these were found to be less pervasive in this sample. The paper concludes with a discussion about the comparative ineffectiveness of teacher and school‐related variables in explaining students' attitudes toward science in this study, in light of design decisions and limitations, to guide future investigations.